Evaluation of two xenobiotic reductases from Pseudomonas putida for their suitability for magnetic nanoparticle‐directed enzyme prodrug therapy as a novel approach to cancer treatment. Issue 10 (26th September 2020) - Ball, Patrick; Halliwell, Jennifer; Anderson, Simon; Gwenin, Vanessa; Gwenin, Christopher
Abstract: Directed enzyme prodrug therapy (DEPT) is a cancer chemotherapy strategy in which bacterial enzymes are delivered to a cancer site before prodrug administration, resulting in prodrug activation at the cancer site and more localized treatment. A major limitation to DEPT is the poor effectiveness of the most studied enzyme for the CB1954 prodrug, NfnB from Escherichia coli, at concentrations suitable for human use. Much research into finding alternative enzymes to NfnB has resulted in the identification of the Xenobiotic reductases, XenA and XenB, which have been shown in the literature to reduce environmentally polluting nitro‐compounds. In this study, they were assessed for their potential use in cancer prodrug therapy strategies. Both proteins were cloned into the pET28a+ expression vector to give the genetically modified proteins XenA‐his and XenB‐his, of which only XenB‐his was active when tested with CB1954. XenB‐his was further modified to include a cysteine‐tag to facilitate direct immobilization on to a gold surface for future magnetic nanoparticle DEPT (MNDEPT) treatments and was named XenB‐cys. When tested using high‐performance liquid chromatography (HPLC), XenB‐his and XenB‐cys both demonstrated a preference for reducing CB1954 at the 4‐nitro position. Furthermore, XenB‐his and XenB‐cys successfully induced cell death in SK‐OV‐3 cells when combined with CB1954. This led to XenB‐cys being identified as a promising candidate for use in future MNDEPT treatments. Abstract : Both recombinant XebB‐his and XenB‐cys successfully induced cell death in SK‐OV‐3 cells when combined with the nitroaromatic prodrug CB1954. This led to XenB‐cys being identified as a promising candidate for use in cancer prodrug therapy treatments.